2015
DOI: 10.1109/tmi.2015.2440253
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanically Constrained Surface Registration: Application to MR-TRUS Fusion for Prostate Interventions

Abstract: In surface-based registration for image-guided interventions, the presence of missing data can be a significant issue. This often arises with real-time imaging modalities such as ultrasound, where poor contrast can make tissue boundaries difficult to distinguish from surrounding tissue. Missing data poses two challenges: ambiguity in establishing correspondences; and extrapolation of the deformation field to those missing regions. To address these, we present a novel non-rigid registration method. For establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The non-rigid FFD transformation with high degrees of freedom (DoFs) offered too much flexibility and the algorithm incorrectly registered the prostate surface to segmentation noise. Similarly, other studies have reported increased TRE for unconstrained non-rigid registration methods over rigid registration (Cool et al, 2011; Khallaghi et al, 2015b) and that unconstrained, deformable registration did not show significant improvements over affine registration (Delongchamps et al, 2013; Fedorov et al, 2015). We have seen analogous results when performing intensity-based multi-modal brain registration with an SDM (Onofrey et al, 2016), where rigid registration can outperform unconstrained non-rigid registration due to noisy data.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…The non-rigid FFD transformation with high degrees of freedom (DoFs) offered too much flexibility and the algorithm incorrectly registered the prostate surface to segmentation noise. Similarly, other studies have reported increased TRE for unconstrained non-rigid registration methods over rigid registration (Cool et al, 2011; Khallaghi et al, 2015b) and that unconstrained, deformable registration did not show significant improvements over affine registration (Delongchamps et al, 2013; Fedorov et al, 2015). We have seen analogous results when performing intensity-based multi-modal brain registration with an SDM (Onofrey et al, 2016), where rigid registration can outperform unconstrained non-rigid registration due to noisy data.…”
Section: Discussionsupporting
confidence: 58%
“…Localizing these landmarks was challenging due to the ambiguous delineation of the prostate gland surface in parts of the TRUS imaging with little tissue contrast. We found that patient-specific cysts and other “cyst-like” anatomical structures appearing in both the MR and TRUS images were the most reliable to localize, and these types of landmarks have also been used to calculate TRE in other studies (Hu et al, 2012, 2015; Fedorov et al, 2015; Khallaghi et al, 2015b,a). The 29 identified landmarks used in Sec.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations